Determinan Tingkat Pemahaman Mahasiswa Akuntansi terhadap International Financial Reporting Standard - Suherma, Linda; Soraya, Soraya (Jurusan Akuntansi Politeknik Negeri Pontianak, 2023)
This study aims to determine emotional intelligence, spiritual intelligence, learning behavior, and learning interest affect the level of understanding of accounting students about IFRS. This research is an empirical study on Accounting Department Students at the Pontianak State Polytechnic. The population of this research is the fourth semester students of the Diploma III study program at the Polytechnic Accounting Department. The variables observed/measured in this study were independent variables namely Emotional Intelligence (X1), Spiritual Intelligence (X2), Learning Behavior (X3), and Learning Interest (X4). While the devenden variable is the level of understanding of IFRS (Y). The research variables will be given a Likert scale of 1-5 with an assessment of the perception of statements from strongly disagree (scale 1) to strongly agree (scale 5). The data analysis technique in this study was quantitative analysis using data quality tests, classical assumption tests, hypothesis testing and multiple linear regression analysis with the SPSS program. The results of this study indicate that emotional intelligence, spiritual intelligence, learning behavior, and learning interest do not affect the level of students' understanding of IFRS. This is evidenced by the significance value of the t test (partial test) of the four independent variables which are above 0.05.